MO017: The Impact of Pre-Transplantation Nephrectomy on Quality of Life in Patients With Autosomal Dominant Polycystic Kidney Disease. (3rd May 2022) - Geertsema, Paul; Gansevoort, Ronald; Leliveld-Kors, Annemarie; De Fijter, Johan W; Dekker, Shosha; Meijer, Esther; Pol, Robert; Sanders, Jan-Stephan; Casteleijn, Niek F
Abstract: BACKGROUND AND AIMS: In autosomal dominant polycystic kidney disease (ADPKD), the enlarged kidneys can cause clinical problems, for instance pain or gastro-intestinal complaints, recurrent infections, or cause a lack of space for a kidney transplant. In selected ADPKD patients, a nephrectomy is required in the work-up for a kidney transplantation. Currently, it is unknown how this procedure affects quality of life (QoL), nor how leaving both kidneys in situ influences wellbeing. The aim of this study was to investigate the impact of pretransplantation nephrectomy on quality of life in APDKD patients. METHOD: In this retrospective cohort study all ADPKD patients, ≥18 years, who received a kidney transplantation in 2 ADPKD expertise centers in the Netherlands (UMC Groningen and UMC Leiden) between January 2000 and January 2016, were asked to participate. Of these two centers, one has a restrictive approach, wherein a unilateral procedure is only performed when strict indications are met, and one a proactive approach, wherein a bilateral procedure is performed routinely in the work-up for transplantation. Data were collected on patients characteristics, date of nephrectomy, date of kidney transplantation and QoL. QoL was assessed using validated questionnaires (the SF-36, PHQ-9 and ADPKD-Impact Score) on three different time points (12 months before transplantation, 12 months after transplantation and date of filling out the questionnaire). Patients were followed for at least 24 months after transplantation. RESULTS: 321 ADPKD (61 ± 9 years, 57.9% male) patients were included. The minority of patients ( n  = 99, 30.8%) underwent native nephrectomy in preparation for transplantation, of which 43 patients (13.4%) underwent bilateral nephrectomy. Lack of space was the most common indication for nephrectomy (68.7%), followed by recurrent cyst infection (18.2%) and refractory pain complaints (9.1%). Age, sex and comorbidities did not differ before transplantation between patients who would later undergo a pretransplantation nephrectomy when compared to those who would not undergo this procedure, except for QoL. The SF-36 physical component score (PCS) and mental component score (MCS) were lower in the nephrectomy group vs. no nephrectomy group (33.8 versus 38.4, P  = 0.003; 48.7 versus 51.7, P  = 0.04, respectively). In addition, the PHQ-9 and ADPKD-IS were significantly lower in patients who would later undergo a pre-transplantation nephrectomy compared to patients who would not undergo this procedure ( P  = 0.01, P  = 0.01, respectively). After transplantation the PCS and MCS improved significantly in both groups, with this improvement in PCS and MCS being significantly more in patients who had a pretransplant nephrectomy compared with those who did not have a nephrectomy (change in PCS 17.3, P < 0.001 versus 13.4, P < 0.001; change in MCS 9.7, P < 0.001 versus 4.5, P < 0.001). Similar findings were noted for the PHQ-9 and APDKD-IS. At the end of follow-up, 7.9 ± 4.6 years after transplantation, PCS and MCS were still better in both groups (PCS 45.9, P < 0.001 versus 49.7, P < 0.001; MCS 57.4, P < 0.001 versus 55.1, P < 0.001, respectively). No differences in the PCS, MCS, PHQ-9 and ADPKD impact scores were observed between both expertise centers as well as in patients who underwent unilateral versus bilateral nephrectomy. CONCLUSION: This study shows that ADPKD patients who underwent a pretransplantation nephrectomy experienced more complaints compared with patients without nephrectomy. After nephrectomy and transplantation, QoL significantly improved in these patients, resulting in a similar QoL level in all transplanted ADPKD patients on short as well as long-term follow-up. Bilateral nephrectomy had no additional benefit on QoL compared with unilateral nephrectomy. Together, this indicates that a restrictive approach, wherein a unilateral procedure is performed only when strict indications are met, may improve QoL in these patients and is therefore justified.